Implementation Of Business Intelligence Framework For Malaysian Halal Food Manufacturing Industry Towards Initiate Strategic Financial Performance Management - Mohamad, Abdul Karim; Jayakrishnan, Mailasan; Azmi, Fadhlur Rahim; Abdullah, Abu (Growing Science, 2018)

(untitled)
The utilization of Business Intelligence (BI) to yield financial management among manufactures has been one of the main advantages of managing businesses through strategized financial performance.The BI can be conceptualized as a decision-making process,which is an emerging topic within technology management and financial decision making.Furthermore,such factors influencing the adoption of this type of strategized decision-making process are under extensive investigation.The main objective of this research is to develop a BI framework to provide a data analytics and action plan to help Malaysian Halal Food Manufacturing Industry (MHFMI) strategize financial performance.The specific objective of the study is to assess and validate the relationship between the adoption of BI and MHFMI.The methodology of the study starts with the theory adoption of BI parameters and methods,followed by the development of the adopted and adapted theoretical models using the conceptual framework developed and MHFMI involvement into the strategic financial performance management.The managers of the MHFMI is requested to provide the necessary information about their companies,perception of BI and financial performances.Reliability analysis is used to validate the constructs and test measurements in variance.The study applies regression analysis to determine the effects of different decision making strategies on BI.The research output indicates that the BI data analytics and the action plan as well as the conceptual framework could improve the financial performance by the adoption and the adaptation of the conceptualized strategy among MHFMI.